2021
DOI: 10.1186/s12955-021-01709-9
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis and measurement invariance of the English, Mandarin, and Malay versions of the SF-12v2 within a representative sample of the multi-ethnic Singapore population

Abstract: Background The Short Form Health Survey (SF-12v2) is an increasingly popular measure of health-related quality of life (HRQoL) in Singapore. In order to examine whether the SF-12v2 was appropriate for use in the population, the factor structure and validity of the English, Mandarin, and Malay versions were assessed in a representative sample of the general population of Singapore. Methods 6126 respondents were recruited for the Singapore Mental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…However, it has been found that age positively correlates with workers' mental health. This result is in line with the research by Lau et al [ 44 ] and Shamshirgaran et al [ 68 ]. According to the findings of Lau et al [ 44 ], older people had poorer physical health than those aged 18 to 34 years, but older people had better mental health related quality of life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it has been found that age positively correlates with workers' mental health. This result is in line with the research by Lau et al [ 44 ] and Shamshirgaran et al [ 68 ]. According to the findings of Lau et al [ 44 ], older people had poorer physical health than those aged 18 to 34 years, but older people had better mental health related quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in line with the research by Lau et al [ 44 ] and Shamshirgaran et al [ 68 ]. According to the findings of Lau et al [ 44 ], older people had poorer physical health than those aged 18 to 34 years, but older people had better mental health related quality of life. Similarly, the findings of Shamshirgaran et al [ 68 ] supported the notion that physical health deteriorated with age while mental health improved.…”
Section: Discussionsupporting
confidence: 93%
“…The Short Form Health Survey version 2 (SF-12v2) is a 12-item questionnaire designed to assess HRQoL amongst patient populations and replicates summary scores of the SF-36 [ 70 ]. This questionnaire has been validated in the Singapore population [ 44 ]. The 12-items cover eight sub-domains: general health, physical functioning, role physical, bodily pain, vitality, social functioning, role emotional, and mental health.…”
Section: Methodsmentioning
confidence: 99%
“…My third study, a cross-sectional survey study, found that general mental health was poorer in YOD, compared with UOD. This may be an effect of age, as was reflected by the findings of a population-wide study conducted in Singapore, which also found poorer psychological health in young adults (260). In addition, diabetes-distress levels in YOD were significantly higher than in UOD, especially with emotional-related, regimen-related and interpersonal distress.…”
Section: Poorer Psychological Health and Its Effect On Dietmentioning
confidence: 97%
“…The survey instruments used in this study have been previously used in Singapore (244,(260)(261)(262). Therefore, only pre-testing of the survey was carried out for the purpose of developing an interview guide to be used in interviewer training.…”
Section: Pre-testingmentioning
confidence: 99%